Quantitative Risk Assessment (QRA) Prenatal Mercury Exposure of Whitening Cosmetic and Infant Neurodevelopmental Risk - Hasriwiani Habo Abbas; Yuliati Yuliati; Masayuki Sakibara (Journal of Public Health and Pharmacy, 2025)
ntroduction: Mercury compounds are divided into elemental mercury, inorganic mercury, and organic mercury. Exposure to mercury through both direct and indirect pathways can have serious impacts on environmental and health issues, especially sensitive populations such as pregnant women, infants, and children. According to the Global Nielsen institution, 45% of women in Indonesia use whitening cosmetics. It should be noted that the content of whitening cosmetics contains mercury and its derivatives. Pregnant women are exposed to mercury through the use of cosmetics and the consumption of seafood. The impact caused if accumulated in the placenta will cause neonatal neurodevelopmental risk. This study aimed to analysed the quantitative risk assessment of prenatal mercury exposure and neurodevelopmental risk. Methods: The study design is an observational analytic with a cross-sectional study. Statistical analysis of Hg concentration in scalp hair samples was performed using SPSS software. The correlation between Hg concentration in scalp hair and skin whitening cosmetics was determined by chi-square correlation analysis, with p < 0.05 considered significant. The quantitative risk assessment (QRA) method analyses hazard identification, assessment exposure, hazard characterization, and risk characterization. The sample used was 20 pregnant women and 20 babies. The mercury concentration in the scalp hair of pregnant women and their babies will be examined in the BBLK Laboratory. Results: The results of this study indicate that hazard identifications were mercury concentrations in the scalp hair of pregnant women is average of 7.04 (range 0.18-41.70 ppm, the mercury concentration in scalp hair is average of 0.71 (range 0.24-1.68), mercury whitening cosmetic is average 17.34 (range 3.5-86.0 ppm). Hazard characteristics are divided according to HBM 3 categories: normal at 60%, alert at 15%, and high at 25% for mercury concentration in pregnant women. In comparison, the baby concentration is divided into two categories: normal 70% and alert 30%. Risk characteristics found that around nine people, or 45% of babies, experienced the risk of neurodevelopmental symptoms, and mothers exposed to mercury had an impact on their babies. Conclusion: This study highlights the occurrence of Hg in skin-whitening cosmetics and the accumulation of Hg in the human body through their application. There is a correlation between mercury in pregnant women's scalp hair and the mercury concentration in their babies. Babies exposed to mercury with alert concentration levels have a neurodevelopmental risk. Therefore, it is better not to use whitening cosmetics during prenatal periods because mercury exposure can affect the baby.